Evaluation of coronal microleakage of mineral trioxide aggregate plug-in teeth with short roots prepared for post placement using bacterial penetration technique - A A Khademi; N Shekarchizade (Wolters Kluwer Medknow Publications, 2016)
Context: Two of the problems of the placement of posts in teeth with short roots are to determine the minimum length of the canal obturation material at the apical third of the root canal and removal of all the canal obturation material from the root canal during post space preparation. Aim: The aim of the present study was to compare the coronal microleakage of mineral trioxide aggregate (MTA) plug and gutta-percha in short roots prepared for post placement using the bacterial penetration technique. Materials and Methods: In the presentin vitro study, 40 extracted single-rooted anterior teeth measuring 13 mm in root length were selected. Since the roots were short, 3 mm of the root length was allocated to the root canal obturation material and 10 mm of the root length was allocated to post placement. After preparation of the root canals, post spaces were prepared and the samples were randomly divided into two groups of gutta-percha and MTA. Fifteen root canals were obturated with gutta-percha and the post space was immediately prepared, with 3 mm of gutta-percha remaining in the apical end of the root canal. In 15 teeth, MTA plugs were placed, which measured 3 mm in length. The samples were placed in the Enterococcus faecalis bacterial microleakage system for 120 days. The time for the turbidity of each sample was recorded. Data were analyzed with Fisher's exact test. Results: During the study period, turbidity was observed in all the gutta-percha samples and in only four MTA samples, with statistically significant differences between the two groups (P< 0.001). Conclusion: Based on the results, MTA exhibited much better sealing ability compared to gutta-percha as a root canal obturation material in teeth with short roots.